Determinants of high-risk sexual behavior during post-exposure prophylaxis to prevent HIV infection. - Golub, Sarit A; Rosenthal, Lisa; Cohen, Daniel E; Mayer, Kenneth H (AIDS and behavior, 2008)
Men who have sex with men (MSM) receiving non-occupational post-exposure prophylaxis (NPEP) to prevent HIV transmission completed interview-assisted questionnaires regarding high-risk behavior in the 6 months prior to NPEP and during the 28-day NPEP period. 21% of participants reported unprotected sex during NPEP, and 11% reported unprotected sex with HIV-positive or HIV status unknown partners. In univariate analyses, unprotected sex during NPEP was associated with prevention fatigue, depression, loss of loved ones to HIV, and a history of engagement with HIV/AIDS service organizations, e.g., receiving services from an HIV-related agency, donating money to HIV-related causes, and reading HIV-related magazines. Logistic regression analyses revealed that the strongest predictor of risk-taking during NPEP was HIV engagement. These data underscore the importance of combining chemoprophylaxis with behavioral interventions that support risk-reduction. Such interventions should not assume that those most engaged with HIV/AIDS service organizations are less likely to engage in risk behavior.
Keywords: Adenine; Anti-HIV Agents; Deoxycytidine; Drug Therapy, Combination; HIV Infections; Homosexuality, Male; Humans; Interviews as Topic; Lamivudine; Male; Organophosphonates; Questionnaires; Reverse Transcriptase Inhibitors; Risk Factors; Risk-Taking; Sexual Partners; Treatment Outcome